A Library Book for Bear - Becker, Bonny; Denton, Kady MacDonald (Somerville, Massachusetts : Candlewick Press, 2014)
Although he sees no need for more books to read, Bear agrees to accompany Mouse to the library.
Accelerated Reader AR